Bài 2: Nhân đa thức với đa thức

BN

Thực hiện các phép tính sau:

a) (x2 -1) (x2 + 2x)

b) (2x-1)(3x+2)(3-x)

c) (x+3)(x2 + 3x-5)

d) (x+1)(x2 - x+1)

e) (2x3 - 3x-1)(5x+2)

f) (x2 - 2x+3)(x-4)

g) (4x-1)(3x+1)-5x(x-3)-(x-4)(x-3)

h) (5x-2)(x+1)-3x(x2-x-3)-2x(x-5)(x-4)

NT
14 tháng 8 2020 lúc 11:28

a) Ta có: \(\left(x^2-1\right)\left(x^2+2x\right)\)

\(=x^4+2x^3-x^2-2x\)

b) Ta có: \(\left(2x-1\right)\left(3x+2\right)\left(3-x\right)\)

\(=\left(6x^2+4x-3x-2\right)\left(3-x\right)\)

\(=\left(6x^2+x-2\right)\left(3-x\right)\)

\(=18x^2-6x^3+3x-x^2-6+2x\)

\(=-6x^3+17x^2+5x-6\)

c) Ta có: \(\left(x+3\right)\left(x^2+3x-5\right)\)

\(=x^3+3x^2-5x+3x^2+9x-15\)

\(=x^3+6x^2+4x-15\)

d) Ta có: \(\left(x+1\right)\left(x^2-x+1\right)\)

\(=x^3+1\)

e) Ta có: \(\left(2x^3-3x-1\right)\left(5x+2\right)\)

\(=10x^4+4x^3-15x^2-6x-5x-2\)

\(=10x^4+4x^3-15x^2-11x-2\)

f) Ta có: \(\left(x^2-2x+3\right)\left(x-4\right)\)

\(=x^3-4x^2-2x^2+8x+3x-12\)

\(=x^3-6x^2+11x-12\)

g) Ta có: \(\left(4x-1\right)\left(3x+1\right)-5x\left(x-3\right)-\left(x-4\right)\left(x-3\right)\)

\(=12x^2+4x-3x-1-5x^2+15x-\left(x^2-7x+12\right)\)

\(=7x^2+16x-1-x^2+7x-12\)

\(=6x^2+23x-23\)

h) Ta có: \(\left(5x-2\right)\left(x+1\right)-3x\left(x^2-x-3\right)-2x\left(x-5\right)\left(x-4\right)\)

\(=5x^2+5x-2x-2-3x^3+3x^2+9x-2x\left(x^2-9x+20\right)\)

\(=-3x^3+8x^2+12x-2-2x^3+18x^2-40x\)

\(=-5x^3+26x^2-28x-2\)

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
NT
Xem chi tiết
NT
Xem chi tiết
PT
Xem chi tiết